Genome cloning and genetic evolution analysis of eight duck-sourced novel goose parvovirus strains in China in 2023 - Zhan, Guangjian; Liu, Nan; Fan, Xiaole; Jiang, Wansi; Yuan, Mengxue; Liu, Yunwang; Dong, Shishan (Frontiers in Microbiology, 2024)
Introduction There are three major categories of waterfowl parvoviruses, namely goose parvovirus (GPV), Muscovy duck parvovirus, and novel goose parvovirus (NGPV). NGPV can infect both Cherry Valley ducks and mule ducks, resulting in short beaks and dwarfism syndrome, and the incidence of short beaks and dwarfism syndrome rises annually, posing a significant threat to the waterfowl breeding and the animal husbandry. Therefore, clarifying the biological characteristics and genetic evolution of NGPV is very important for the prevention and control of NGPV. Methods Ducks with short beaks and dwarfism syndrome from Shandong and Henan Province were investigated by dissection and the tissue samples were collected for study. The NGPV genome was amplified by PCR, and the genome was analyzed for genetic evolution. Results Eight strains of NGPV were isolated, which were designated as HZ0512, HZ0527, HZ0714, HZ0723, HZ0726, HZ0811, HZ0815, and HN0403. The nucleotide homology among these strains ranged from 99.9% to 100%. The eight strains, along with other NGPVs, belong to GPV. The eight strains showed a 92.5%–98.9% nucleotide homology with the classical GPV, while a 96.0%–99.9% homology with NGPV.Therefore, it can be deduced that there have been no major mutations of NGPV in Shandong and Henan provinces in recent years. Discussion This study lays a theoretical foundation for further studying the genetic evolution and pathogenicity of NGPV, thereby facilitating the prevention and control of NGPV.